2007
DOI: 10.1523/jneurosci.4854-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Leads to Tau Hyperphosphorylation through Inhibition of Phosphatase Activity by Hypothermia

Abstract: Postoperative cognitive dysfunction, confusion, and delirium are common after general anesthesia in the elderly, with symptoms persisting for months or years in some patients. Even middle-aged patients are likely to have postoperative cognitive dysfunction for months after surgery, and Alzheimer's disease (AD) patients appear to be particularly at risk of deterioration after anesthesia. Several investigators have thus examined whether general anesthesia is associated with AD, with some studies suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
327
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(368 citation statements)
references
References 73 publications
27
327
4
3
Order By: Relevance
“…It is believed that among all these protein phosphatases, PP2A likely plays the most important role in mediating tau hyperphosphorylation in AD neurons (Liu et al 2005). Studies have shown that starved mice, reduced glucose metabolism, and anesthesia could lead to tau phosphorylation by inhibition of PP2A, indicating the importance of PP2A in regulation of tau phosphorylation (Planel et al 2001(Planel et al , 2004(Planel et al , 2007. In our studies, there was no change in the expression level of PP2A catalytic unit between all four groups of AGS.…”
Section: Discussioncontrasting
confidence: 47%
“…It is believed that among all these protein phosphatases, PP2A likely plays the most important role in mediating tau hyperphosphorylation in AD neurons (Liu et al 2005). Studies have shown that starved mice, reduced glucose metabolism, and anesthesia could lead to tau phosphorylation by inhibition of PP2A, indicating the importance of PP2A in regulation of tau phosphorylation (Planel et al 2001(Planel et al , 2004(Planel et al , 2007. In our studies, there was no change in the expression level of PP2A catalytic unit between all four groups of AGS.…”
Section: Discussioncontrasting
confidence: 47%
“…To avoid transient artifactual changes in tau phosphorylation, 3xTg-AD mice were sacrificed by decapitation without anesthesia, 21 and the brain was rapidly dissected on ice. Samples were snap frozen and stored at À80 C. Frozen tissues were homogenized in radioimmunoprecipitation assay buffer [50 mmol/L Tris-HCl (pH 7.4), 1 mmol/L EDTA, 150 mmol/L NaCl, 1% Nonidet P-40, 0.25% C 24 H 39 NaO 4 , 1 mmol/L NaVO 3 , 1 mmol/L NaF, 1 mmol/L phenylmethylsulfonyl fluoride, and 10 mg/mL protease inhibitor cocktail (Sigma-Aldrich)] and centrifuged at 135,000 Â g for 45 minutes at 4 C. The radioimmunoprecipitation assayeinsoluble pellet from cortical homogenates was resuspended in one volume of 70% formic acid, sonicated, and centrifuged at 23,500 Â g for 15 minutes at 4 C. The supernatant was collected (formic acid fraction containing insoluble proteins) and neutralized in 20 volumes of neutralization buffer containing 1 mol/L of Tris base and 0.5 mol/L of Na 2 PO 4 .…”
Section: Western Blot Analysis and Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Other cellular targets should sense the change in biochemical potential in a similar fashion, and in fact this has been demonstrated, for example, for neurofilaments (Ishihara et al 2001). An overall shift of phosphorylation potential can occur, for example, by a temperature drop during anesthesia or experimental diabetes, which reduces the activity of PP2a and thus mimics an Alzheimer-like phosphorylation state on Tau, reminiscent of the effects of aging (Planel et al 2007a;Planel et al 2007b;Veeranna et al 2009). Conversely, heat stress and oxidative stress activate PP2a and thus generate a low state of Tau phoshorylation, which protects against DNA damage (Davis et al 1997;Sultan et al 2011).…”
mentioning
confidence: 99%